First-Principles Study on the Structural and Electronic Properties of Double $N$ Atoms Doped-Rutile $TiO_2$ (Journal of Atomic and Molecular Sciences, 2010)
The electronic structure of rutile $TiO_2$ doped with double nitrogen atoms is studied by the plane-wave ultrasoft pseudopotential method based on the first-principles density functional theory. It has been used to analyze the effect of three doping positions of double $N$ on the relevant band structure. The calculation demonstrates that there exist additional states in the band gap when doping of the rutile $TiO_2$ with $N$ atoms, and the gap become narrowing. The results imply that the doped two $N$ atoms in the adjacent position form a more intermediate stable level, and the total energy is the minimum.